A Python script repository for multiscale modelling with Direct FE2 in Abaqus - Kirk Ming Yeoh; Karthikayen Raju; Vincent Beng Chye Tan (SoftwareX, 2025)
While computational homogenization via FE2 is a useful multiscale modelling tool for many fields, conventional implementations often require an expert level of user involvement. To address this, this work presents a Python script repository to easily set up Direct FE2 input files for multiscale modelling in Abaqus. The scripts take in user inputs defining the macroscale problem along with its microscale RVE and returns an Abaqus input file that can be readily submitted for analysis. As Direct FE2 uses only functions which are readily available in Abaqus to perform computational homogenization, no user-defined subroutines are required. This repository seeks to provide researchers in various fields ease of access to multiscale modelling as a tool to enhance their work. Furthermore, it aims to foster collaboration between researchers working on the Direct FE2 method and further promote its development.